“Literary Memorials”: The Great War Regimental Histories, 1919-1939 - Cook, Tim (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2002)
AbstractWhile the Canadian Corps earned a reputation as one of the finest fighting formations on the Western Front during the First World War, and had an efficient publicity machine under the guiding hand of Lord Beaverbrook to propagate their deeds, the Canadian government was slow to codify this reputation in postwar historical texts. The Official History was delayed for nearly two decades and veterans were bitterly disappointed in being denied a comprehensive account of their battles. As a result, regiments took it upon themselves to craft their own histories. Although now largely ignored by historians, this genre of historical writing documented the actions of the unit during the war and served as a tool to commemorate fallen comrades. The regimental histories are important texts within the canon of Canadian military historiography, offering matchless insight into the events and social history of the Great War, as well as into the post-war efforts of combatants and their families to find meaning for this cataclysmic event.